2021
DOI: 10.1002/adhm.202101244
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Mimics of Antimicrobial Peptides for the Targeted Therapy of Multidrug‐Resistant Bacterial Infection

Abstract: Antibacterial materials are highly demanded in treatment of bacterial infection, especially severe ones with multidrug-resistance. Herein, pH-responsive polypeptide, i.e., poly-L-lysine modified by 1-(propylthio)acetic acid-3-octylimidazolium and citraconic anhydride (PLL-POIM-CA), is synthesized by post-polymerization modification of poly-L-lysine (PLL) with 1-(propylthio)acetic acid-3-octylimidazolium (POIM) and citraconic anhydride (CA). It is observed that PLL-POIM-CA is stable under normal physiological c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…However, studies have shown that the other major problem of most antibacterial drugs was their poor permeability into bacterial biofilms. 35,36 Bacterial biofilm is a membrane formed by bacteria in the process of growth to adapt to the environment. 37 In order to test the ability of FSDMSsF NPs to eliminate bacterial biofilm, a biofilm removal experiment was designed (Fig.…”
Section: Performance In Directional Removal Of Biofilmsmentioning
confidence: 99%
“…However, studies have shown that the other major problem of most antibacterial drugs was their poor permeability into bacterial biofilms. 35,36 Bacterial biofilm is a membrane formed by bacteria in the process of growth to adapt to the environment. 37 In order to test the ability of FSDMSsF NPs to eliminate bacterial biofilm, a biofilm removal experiment was designed (Fig.…”
Section: Performance In Directional Removal Of Biofilmsmentioning
confidence: 99%
“…Gong et al synthesized a pH-responsive polypeptide (PLL-POIM-CA), containing poly- l -lysine (PLL) enhanced by 1-(propylthio) acetic acid-3-octylimidazolium (POIM) and citraconic anhydride (CA), which mimicked antimicrobial peptides . These polypeptides are helpful as a handy treatment for multi-drug-resistant bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Typical antimicrobial polymers stand out for their chemical stability; however, in the last few years, self-degradable and biodegradable polymer systems are also needed to reduce not only antimicrobial pollution in the environment but also degradability in vivo minimizes side effects in the body after eradicating bacterial infection [ 22 , 23 , 24 ]. The biodegradability of the polymers can be achieved by the presence or incorporation of labile chemical linkages such as ester, amide and carbonate bonds.…”
Section: Introductionmentioning
confidence: 99%